Clinical Course and Risk Factors of Diabetic Retinopathy in Patients with Type 2 Diabetes Mellitus in Korea - Jae-Seung Yun; Tae-Seok Lim; Seon-Ah Cha; Yu-Bae Ahn; Ki-Ho Song; Jin A Choi; Jinwoo Kwon; Donghyun Jee; Yang Kyung Cho; Yong-Moon Park; Seung-Hyun Ko (Diabetes & Metabolism Journal, 2016)
BackgroundWe investigated clinical course and risk factors for diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM).MethodsA total of 759 patients with T2DM without DR were included from January 2001 to December 2004. Retinopathy evaluation was performed at least annually by ophthalmologists. The severity of the DR was classified into five categories according to the International Clinical Diabetic Retinopathy Severity Scales.ResultsOf the 759 patients, 523 patients (68.9%) completed the follow-up evaluation. During the follow-up period, 235 patients (44.9%) developed DR, and 32 patients (13.6%) progressed to severe nonproliferative DR (NPDR) or proliferative DR (PDR). The mean duration of diabetes at the first diagnosis of mild NPDR, moderate NPDR, and severe NPDR or PDR were 14.8, 16.7, and 17.3 years, respectively. After adjusting multiple confounding factors, the significant risk factors for the incidence of DR risk in patients with T2DM were old age, longer duration of diabetes, higher mean glycosylated hemoglobin (HbA1c), and albuminuria. Even in the patients who had been diagnosed with diabetes for longer than 10 years at baseline, a decrease in HbA1c led to a significant reduction in the risk of developing DR (hazard ratio, 0.73 per 1% HbA1c decrement; 95% confidence interval, 0.58 to 0.91; P=0.005).ConclusionThis prospective cohort study demonstrates that glycemic control, diabetes duration, age, and albuminuria are important risk factors for the development of DR. More aggressive retinal screening for T2DM patients diagnosed with DR should be required in order to not miss rapid progression of DR.